ANALISIS NARATIF PESAN DAKWAH DALAM FILM TARUNG SARUNG - Ilham Ilham; Junaidi Junaidi (KOLONI, 2022)
Film is one of the mass communication media that is used to convey various kinds of messages or information. Like the film, fighting gloves. A wide-screen film with the genre of drama and action, it contains da'wah messages. This film was inspired by Makassar culture, namely Tarung Sarong, which in this film collaborates between culture and religion so that goodness can be born because it is accompanied by religion, as in the story of this Tarung Sarong film. This film tells the story of a wealthy businessman's son who thinks money is everything, so that makes him not believe in God. Departing from this phenomenon, the authors decided to conduct a more in-depth study of the film Tarung Sarong in order to understand the da'wah messages contained in the film with Tzvetan Todorov's narrative analysis. The purpose of this study was to find out the narrative analysis of da'wah messages in the film Tarung Sarong. The benefits of this research are theoretically expected to be an interesting study in conveying da'wah messages which are expected to make a positive contribution as well as the development of knowledge about narrative analysisThe type of research used is a type of qualitative research with a narrative approach, where the author makes observations, namely observing and developing observational power about the object to be studied and analyzing it using Tzvetan Todorov's narrative analysis. The results of this study indicate that the Tarung Sarong film has messages of preaching aqidah, morals, and sharia. We can see the message of preaching the aqidah (remembrance by saying istighfar) at the beginning of the film Tarung Sarong. We can see the message of preaching morality (saying greetings to fellow Muslims) at the beginning of the film Tarung Sarong. We can see the message of preaching akiqah (belief in God), in the middle. We can see the message of Islamic akwah (prayer) in the middle. We can see the message of preaching morals (saying greetings, being grateful, and helping each other), we can see in the middle. Moral da'wah messages (always be grateful, help each other and sincerely this da'wah message can be seen at the end of the film Tarung Sarong) Keywords:  Narrative Analysis, Dakwah Messages, in the Film Tarung Sarong.